Cyclodextrin-Derived Porous Liquids Enabled by In Situ Solvation Shell Formation - Errui Li; Anton S. Pozdeev; Arvind Ganesan; Hongjun Liu; Bo Li; Lilin He; Gergely Nagy; Takeshi Kobayashi; Murillo L. Martins; Yongqiang Cheng; De-en Jiang; Shannon M. Mahurin; et al. (Journal of the American Chemical Society, 2026)
Abstract Porous liquids (PLs) represent a unique platform for molecular separations by combining permanent porosity with liquid-phase mobility. However, it remains a formidable challenge to construct and stabilize PLs with sub-5 Å pores using readily available porous host and liquid media. Here, we report the construction of cyclodextrin (CD)-derived PLs enabled by in situ solvation shell formation. The acid–base neutralization reaction between CD and an organic base was leveraged to generate a thin ionic solvation shell around the CD host, effectively liquefying CD and preventing its segregation in the liquid base medium while preserving accessible molecular-scale cavities. Spectroscopic analysis, neutron scattering, density functional theory calculations, and molecular dynamics simulations collectively confirm the structural evolution and existence of abundant internal porosity in PLs. The unique architectures of CD-derived PLs enable highly selective encapsulation of fluorinated alkanes and significantly enhanced uptake of inert gases. This facile and generalizable strategy enables construction of high-quality PLs with engineered ultramicroporosity to facilitate molecular separations.